THE EVOLUTION OF CLUJ FORTRESS FROM EXTRAMUROS AREA AND THE IMPRINT OF THE GEOSITE IN THE GEOGRAPHICAL LANDSCAPE OF CLUJ-NAPOCA CITY - Paula CODREA; Ioan RUS; Ioan-Aurel IRIMUȘ; Raularian RUSU (Studia Universitatis Babeş-Bolyai: Geographia, 2022)
Cluj Fortress was built by the military garrison of the Habsburg Empire to have a defensive role in tragic periods. The site of its location was chosen possibly due to morphology, the presence of landforms developed on sandstones and conglomerates which led provided conditions for living and development in that place. The evolution of the area from extramuros to intramuros was shaped by the living necessities that the military garrison had to satisfy. By entering the area beyond the walls, “the world down there”, they had access to the means of satisfying their needs, to the necessary substance and energy exchange. The emergence of miserable households, mere holes in the slope, was possible due to the geological structure. They had a negative impact on the geographical landscape, due to the negative look of the slope, but also because of the precarious living conditions of the inhabitants of that area. The development of communities including disfavoured people determined miserable living conditions, while they tried to survive in different manners. By means of the used methodology, the paper highlights the evolution of Cluj Fortress since ancient times until today, and to emphasize the importance of the Fortress site from a scientific and anthropogenic point of view, by means of the geomorphosite inventory list.